The Impact of the Covid-19 Pandemic on Learning Effectiveness and Performance of Health Physical Education Teacher in Banjarmasin City - Risdawati; Tri Irianto; Rahmadi (Kinestetik : Jurnal Ilmiah Pendidikan Jasmani, 2023)
The aim of the study was to describe the impact that occurred during the Covid 19 Pandemic on the Learning Effectiveness and Performance of Sports Health Physical Education Teachers in the City of Banjarmasin. The method used is descriptive qualitative. Data collection uses the distribution of research instruments. This study used 128 PESH teacher respondents and 111 principals/deputy principals and supervisors. The results of this study are that the covid 19 pandemic has positive and negative effects on the covid 19 (X) pandemic variables, on student indicators, teacher indicators, distance learning indicators, physical distancing (lockdown), learning indicators, internet indicators, and smartphone indicators, while variables learning effectiveness (Y1) is an indicator of suitability of learning objectives, an indicator of maximum learning outcomes, an indicator of the interaction process of students with students in the learning environment, an indicator of learning media, an indicator of the interaction of students' processes with learning resources in the learning environment, and for PESH teacher performance variables (Y2) namely indicators of knowing student characteristics, indicators of mastery of learning theory and educational learning principles, indicators of curriculum development, indicators of educational learning activities, indicators of developing student potential, indicators of communicativeness with students, indicators of assessment and assessment, indicators of acting according to religious, legal, social and cultural norms of the nation, indicators showing mature and exemplary personality, indicators of work ethic, high responsibility, pride in being a teacher, indicators of inclusiveness, acting objectively and not discriminatory, indicators of communication with fellow teachers, education staff , parents, students and society, indicators of material mastery, conceptual structures and scientific mindsets that support the subjects taught, indicators of developing professionalism through reflective action. The pandemic has had an impact on learning effectiveness and teacher performance.